Pollination of an endangered Caladenia species (Orchidaceae) by nectar-foraging behaviour of a widespread species of colletid bee. (20th December 2018) - Reiter, Noushka; Bohman, Björn; Batley, Michael; Phillips, Ryan D
Abstract: The geographical range of pollinators is an important factor determining the distribution of plants with specialized pollinator interactions. Furthermore, pollinator availability can be critical for the success of conservation translocations of threatened flora with such interactions. Here, we investigated the pollination biology of the endangered orchid Caladenia versicolor, with the aim of improving management of wild populations and conservation translocations (artificial translocation for conservation). Using portable groups of cultivated plants to attract pollinators, we found that at natural sites C. versicolor is predominantly pollinated by food-foraging males of one species of bee, Leioproctus platycephalus (Colletidae), with only occasional visits from females or other bee species. This apparently high degree of specialization occurred despite the presence of a co-occurring bee community of > 20 species. Although previously thought to be nectarless, gas chromatography-mass spectrometry analysis of labellum secretions revealed that C. versicolor produces meagre quantities of sucrose on the upper surface of the labellum, on which some pollinators appeared to feed. Reproductive success was high in C. versicolor at both natural and translocated sites. Although C. versicolor now has a restricted range, L. platycephalus is found across a broad area of southern Australia. Thus, pollinator availability does not appear to have contributed to the rarity of C. versicolor, but the apparent reliance on L. platycephalus means that the availability of this species needs to be taken into account for conservation management and translocations.